Electrochemically facilitated oxidative C–H amination enables access to fluorescent N9-fused tricyclic xanthines. Issue 19 (9th August 2021) - Yang, Qi-Liang; Li, Yan-Yan; Liu, Ying; Ren, Tian-Xiang; Guo, Liu-Cheng; Wang, Dong-Chao; Xie, Ming-Sheng; Qu, Gui-Rong; Guo, Hai-Ming
Abstract : An electrochemically enabled intramolecular C−H amination route for accessing a broad range of fluorescent N9-fused tricyclic xanthines with various substitution patterns under simple, green, and mild condition is developed. Abstract : In this study, an environmentally benign electrochemical protocol for intramolecular oxidative amination is developed, which offers an efficient and sustainable route to access diverse fused tricyclic systems of pyrido[1, 2- e ]purine-2, 4-dione derivatives with pharmacological interest, exhibiting broad scope and generality (>50 examples, yields up to 99%). This electrochemical strategy features good functional group tolerance and permits access to compounds that were previously not achievable under thermal conditions. The photoluminescence properties of the representative N9-fused tricyclic xanthines have also been investigated.